Vocational High School Students Entrepreneurship: The Success of Family or School Education..? - Arum Biruli Walidaini; Agung Wirnarno (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
Purpose of this research is to • determine entrepreneur attitude of SMK students that have entrepreneurship, • determine role of eductaion in family also the role of eduction in school. Approch of that type used is qualitative. Research object was SMK students had been doing entrepreneur while Wadi. Informant in this research were students, the student's parent, teacher of entrepreneur and headmaster. Data collecting using deep interview technique, observation and documentation also attitude test. The research result shows that entreprenuership attitude of students include high category, education of family has important role to build entrepreneurship attitude in terms of involving children in their business, the role of school limited in supporting development of student's knowledge.